CITRINO: phase 1 dose escalation study of anti-LAG-3 antibody encelimab alone or in combination with anti-PD-1 dostarlimab in patients with advanced/metastatic solid tumours - J. Randolph Hecht; Jean-Marie Michot; David Bajor; Amita Patnaik; Ki Y. Chung; Judy Wang; Gerald Falchook; James M. Cleary; Richard Kim; Anuradha Krishnamurthy; Omkar Marathe; Hagop Youssoufian; et al. (BJC Reports)
Abstract Background Dual programmed cell death protein (ligand)-1 (PD-[L]1) and lymphocyte-activation gene-3 (LAG-3) blockade has demonstrated improved anti-tumour response in some advanced solid tumours. CITRINO, a two-part, Phase 1 dose-escalation study, evaluated encelimab (TSR-033; novel anti-LAG-3) monotherapy and in combination in patients with advanced/metastatic solid tumours. Methods Part 1 (P1) involved dose escalation (20–720 mg Q2W) of encelimab as monotherapy (P1A/B) and with dostarlimab (500 mg Q3W) in patients with previously treated advanced/metastatic solid tumours (P1C). P2 involved cohort expansion in patients with anti-PD-(L)1-naïve microsatellite stable advanced/metastatic colorectal cancer with recommended phase 2 dose (RP2D) of encelimab with dostarlimab as third/fourth-line therapy (P2A), or with dostarlimab, bevacizumab and mFOLFOX6/FOLFIRI as second-line therapy (P2B). Objectives included RP2D, safety/tolerability, efficacy, pharmacokinetics/pharmacodynamics, and exploratory biomarkers. Results Maximum tolerated encelimab dose was not reached; 720 mg Q2W was used for P2 plus dostarlimab 1000 mg Q6W. One dose-limiting toxicity occurred (Grade 2 myasthenia gravis; P1A). No clinical responses were observed in P1; 1 (3%) and 4 (17%) patients achieved partial response in P2A and 2B, respectively. Conclusions Encelimab has a manageable safety profile as a monotherapy and in tested combinations; however, anti-tumour activity was limited. Clinical trial registration NCT03250832.